Palm Oil Supply Chain Performance Analysis in Muara Takung-Kamang Baru Transmigration Area Sijunjung Regency - Andiny Azzahra; Veralianta Br Sebayang (STIE AMKOP, 2026)
This study aims to analyze the supply chain performance and value-added of oil palm commodities in the Muara Takung-Kamang Baru Transmigration Area, Sijunjung Regency. This research utilizes a quantitative approach with the Supply Chain Operation Reference (SCOR), Analytical Hierarchy Process (AHP), and Hayami methods. Sampling was conducted using the snowball sampling technique. The results show that the supply chain structure involves five main actors: input providers, oil palm farmers, collectors (tokei), Koperasi Unit Desa (KUD), and palm oil mills (PKS). Based on the SCOR and AHP analysis, PKS achieved maximum performance levels, while inefficiencies were found upstream, specifically in the asset management efficiency of input providers, as well as the cost and agility aspects of farmers. Most actors prioritize the reliability attribute, except for the tokei, who prioritizes responsiveness. Hayami's value-added analysis indicates that PKS generates a value-added ratio of 10.53%. Additionally, farmers obtain a higher profit margin when selling their harvest to the tokei (36.60%) compared to the KUD (34.33%). This study recommends the need for regular coordination among actors, increasing plantation productivity upstream, and optimizing yield rates downstream.